Effects of real‐time VR clinical practice on reducing the stigma toward dementia among students of occupational therapy: A randomized controlled trial - Ueno, Keita; Tanaka, Hiroyuki; Niki, Kazuyuki; Ueda, Masaya; Tanaka, Ayumi; Yokoi, Katsushi; Naito, Yasuo; Ishii, Ryouhei (PCN reports, 2023)
Aim This study aimed to examine the effects of real‐time online clinical practice using real‐time virtual reality (VR) compared with 2D PC screening on reducing stigma toward dementia, and to investigate the feasibility of online clinical practice using VR. Methods A single‐center, open‐label, randomized controlled trial was conducted. Occupational therapy students were randomized to view occupational therapy evaluation screens for dementia patients using a VR headset or 2D monitor. The Attitudes Toward Dementia Scale (ADS), the Dementia Knowledge Scale (DKS), and Images of the Elderly with Dementia (IED) were assessed before and after the intervention. The level of clinical practice satisfaction and the System Usability Scale (SUS) were also assessed. Results The number of subjects in the intervention and control groups was 10 and 9, respectively. In ADS scores and IED, the main effect was shown in both groups and did not show interactions. In DKS scores, the main effect and interaction were not shown. The VR headset tended to be more usable than the 2D monitor in terms of usability. Satisfaction ratings indicated the characteristics of a realistic clinical experience through real‐time VR viewing. Conclusion Real‐time VR and 2D online clinical practice could reduce the stigma toward dementia, but there were no significant differences between the types. The real‐time VR experience was more similar to actual clinical practice than a 2D PC screening due to the sense of immersion, but issues in blinding and lack of audio and video quality were found. This study shows that real‐time, online clinical practice experiences, including real‐time virtual reality (VR), can positively change attitudes toward dementia. Online clinical practice can be experienced at a distance, and a large group of people can experience the same scene. Real‐time VR has higher usability and the experience is more similar to actual clinical practice than a 2D PC screen due to the amount of information provided by the 360‐degree images and the sense of immersion.